Biochemical study of CymJ, the putative regulator of cyclodextrin metabolism in Klebsiella oxytoca M5a1 (Medical Journal of Indonesia, 2007)
The products of ten genes clustered in two divergently oriented operons are required for the metabolism of cyclic oligoglucosides, the cyclodextrins, by Klebsiella oxytoca. The function of CymJ, the product of the promoter distal gene in one of the operons was studied. Over expression of cymJ in K. oxytoca led to strong reduction of the expression of the cym operons. This repression could be alleviated by addition of high concentration of α-cyclodextrin into the medium. There is a possible relationship between CymJ and CymD since the absence of CymD in a CymD deletion mutant prevented the repression effect of CymJ. An intriguing finding was that the presence of CymJ in large amount in the cell caused severe cell division inhibition leading to retardation of growth. This morphological change was paralleled by a significant increase in the susceptibility of K. oxytoca to ampicillin. (Med J Indones 2007; 16:69-77) Keywords: cym operon, putative regulator, over expression